ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND SWITCHING (PERPINDAHAN MEREK) PADA PRODUK TEH BOTOL SOSRO DI KELURAHAN BINCAR - hamid, azwar (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
The background of the problem in this study is to find out what are the factors that influence Brand Switching on Tehbotol Sosro products. The research problem formulation is whether there is a partial positive effect or simultaneously between product attribute, price, promotion and product inventory variables towards Brand Switching, this research is quantitative research. The data source used is primary data. The data collection technique used was a questionnaire, with a sample of 135 consumers R square of 0.262, which means that 26.2% of the independent variables were dependent on variables, while the remaining 73.8% was influenced by other factors outside of this study. Partial results (t test) state that, product attributes have -thitung (product attributes) -ttable and significance level α (-2.534 -1,978 and 0.012 0.05) means that product attributes have a significant influence on Brand Switching . Price has thitung (price) t table (5,103 1,978) significance level α (0,000 0,05) means that price has a significant influence on Brand Switching. Promotion has tcount ttable or equal to 0.961 1.978 and the significance level obtained is 0.338 α (0.05), which means that the promotion has no significant influence on Brand Switching. Product inventory has t count t table or equal to 2.575 1.978 and the significance level obtained is 0.011 α (0.05), meaning that the product inventory has a significant influence on Brand Switching. The results of the study simultaneously (F test) states that F count F table (12,897 2.44) and the significance level obtained 0,000 α (0.05) means that product attributes, prices, promotions and product inventories have a significant effect on Brand Switching .